WiMAX Tracker (International Journal of Engineering and Computer Science, 2015)
WiMAX stands for Worldwide Interoperability for Microwave Access. Wimax technology is a telecommunication technology which provides wireless transmission.By the help of this technology we can access the internet and other portable devices. It is technology to deliver content over cable and other links at “last mile”. WiMAX has the ability to support various types of applications, such as web browsing, email, and file transfer. WiMAX operates on the same general principles as WiFi -- it sends data from one computer to another via radio signals. A system which is equipped with WiMAX would receive data from the WiMAX transmitting station, probably using encrypted data keys to prevent unauthorized users from stealing access. WiMAX also worked like a wifi but difference in between them is fastest WiFi connection can transmit up to 54 megabits per second under optimal conditions. WiMAX should be able to handle up to 70 megabits per second. The biggest difference isn't speed; it's distance. WiMAX outdistances WiFi by miles. WiFi's range is about 100 feet (30 m). WiMAX will blanket a radius of 30 miles (50 km) with wireless access. The increased range is due to the frequencies used and the power of the transmitter. Of course, at that distance, terrain, weather and large buildings will act to reduce the maximum range in some circumstances, but the potential is there to cover huge tracts of land. WiMax coverage is measured in square kilometers, while that of WiFi is measured in square meters WiMax specifications also provides much better facilities than WiFi, providing higher bandwidth and high data security by the use of enhanced encryption schemes. WiMax can also provide service in both Line Of Sight (LOS) and Non-Line Of Sight (NLOS) Manoj Kumar, IJECS Volume 4 Issue 6 June, 2015 Page No.12587-12594 Page 12588 locations, but the range will vary accordingly. WiMax antennas can "share" a cell tower without compromising the function of cellular arrays already in place. Worldwide Interoperability for Microwave Access (WiMAX) is currently one of the hottest technologies in wireless WiMAX is a standard-based wireless technology that provides high throughput broadband connections over long distance. WiMAX can be used for a number of applications, including “last mile” broadband connections, hotspots and high-speed connectivity for business customers. It provides wireless metropolitan area network (MAN) connectivity at speeds up to 70 Mbps and the WiMAX base station on the average can cover between 5 to 10 km.